2018
DOI: 10.3390/mca23040078
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluid Convective Heat Transfer Enhancement Elliptical Tube inside Circular Tube under Turbulent Flow

Abstract: Heat transfer enhancement employing an elliptical tube inside a circular tube to increase the heat transfer rate without increasing in pressure drop is investigated. The flow rate inside the narrow is in the range of Reynolds number 10,000 to 100,000. Commercial software is used to solve the governing equations (continuity, momentum, and energy) by adopting a finite volume method (FVM). The electrical heater is connected around the circular tube to apply uniform heat flux (3000 W/m2) as a boundary condition. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Another form of the tube design is elliptical tube inside a circular tube. The elliptical annulus tube may improve the friction factor and heat transmission by 6 and 19%, respectively when compared to circular annulus [12], [57]. The Nusselt number and friction factor often increased with decreasing particle diameter but increased with volume concentration.…”
Section: Elliptical Cross-section Tube Heat Exchangermentioning
confidence: 99%
See 1 more Smart Citation
“…Another form of the tube design is elliptical tube inside a circular tube. The elliptical annulus tube may improve the friction factor and heat transmission by 6 and 19%, respectively when compared to circular annulus [12], [57]. The Nusselt number and friction factor often increased with decreasing particle diameter but increased with volume concentration.…”
Section: Elliptical Cross-section Tube Heat Exchangermentioning
confidence: 99%
“…Conversely, Kumar [11] reported the improvement of heat transfer by Al2O3 nanofluid at low volume fraction under turbulent flow inside a pipe of constant wall temperature. In a related work, Danook et al [12] evaluated the heat transfer of nanofluid at Reynolds number between 1×10 4 and 1×10 5 , as a specific transition from laminar to turbulent flow regime.…”
Section: Introductionmentioning
confidence: 99%
“…Heat transfer with convective boundary conditions is implicated in mechanisms like gas turbines, thermal energy storage, nuclear power plants etc.. In this context, some recent studies [26][27][28][29][30][31] are observed in which the study of non-Newtonian fluid flows with peristalsis are conducted in the vicinity of convective conditions.…”
Section: Introductionmentioning
confidence: 99%